Associations between Prematurity, Low Birth Weight, and Residence on the Risk of Newborn Death: A Meta Analysis - Saputri, Chelsy Sumardi; Rizki, Ayun Widya; Flora, Viola Holly; Murti, Bhisma; Wulandari, Ayu Novita (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Newborn mortality is a global issue that requires serious attention from the world of public health. This study aims to analyze the influence of place of residence, premature birth and low birth weight on the incidence of newborn deaths. Subjects and Method: This research is a meta-analysis research using the PRISMA diagram and PICO format. Population: Newborns died. Intervention: Village residence, premature birth, low birth weight. Comparison: City residence, normal birth, normal birth weight. Outcome: Newborn death. Articles were searched using online databases such as PubMed, Google Scholar, Elsevier, Science Direct. Search for articles using the keywords: